2021
DOI: 10.1177/00222429211002183
|View full text |Cite
|
Sign up to set email alerts
|

Complaint Publicization in Social Media

Abstract: Firms are increasingly turning to social media platforms for complaint handling. Past research and practitioners’ reports highlight the benefits of complaint handling on social media, urging firms to provide prompt and detailed responses to complaints. However, little research has explored the possible drawbacks of such practices, especially when responses inadvertently further publicize complaints. Utilizing two unique data sets in a series of observational and quasi-experimental analyses, this research provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 59 publications
2
23
0
Order By: Relevance
“…The airline industry represents a suitable context for this study because (1) it was dramatically affected by the COVID-19 pandemic ( Eurocontrol. , 2021 , Piccinelli et al, 2021 ), (2) social media is an established communication tool for customers to contact airlines ( Golmohammadi et al, 2021 , Wolfe, 2018 , Xu et al, 2019 ), (3) most airline customers’ travel plans were disrupted by the pandemic, which resulted in a large volume of customer support inquiries ( Elliott, 2021 ), and (4) the airline industry is an established research context for brand-related social media research (e.g., Alantari et al, 2022 , Jalali and Papatla, 2019 , Vo et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The airline industry represents a suitable context for this study because (1) it was dramatically affected by the COVID-19 pandemic ( Eurocontrol. , 2021 , Piccinelli et al, 2021 ), (2) social media is an established communication tool for customers to contact airlines ( Golmohammadi et al, 2021 , Wolfe, 2018 , Xu et al, 2019 ), (3) most airline customers’ travel plans were disrupted by the pandemic, which resulted in a large volume of customer support inquiries ( Elliott, 2021 ), and (4) the airline industry is an established research context for brand-related social media research (e.g., Alantari et al, 2022 , Jalali and Papatla, 2019 , Vo et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…A total of 44.3 % of UK-based internet users were active on Twitter in January 2021 ( Kemp, 2021 ). Thus, in line with prior brand-related social media research (e.g., Borah et al, 2020 , Golmohammadi et al, 2021 , Lee, 2021 , Rust et al, 2021 ), Twitter was used as a data source for this study ( Boegershausen et al, 2022 ). Approximately 327,205 tweets were extracted that matched the search criteria (described in detail below) using the social listening tool Pulsar TRAC ( https://www.pulsarplatform.com ).…”
Section: Methodsmentioning
confidence: 99%
“…Rodrigues Gutierrez et al ( 2022 ) also found evidence from surveying business-to-business salespeople in various industries that social media positively influences sales processes. There can also be downsides to social media use, one of which was identified by Golmohammadi et al ( 2021 ), who showed that by using social media to deal with customer complaints, firms might inadvertently highlight the complaint, and this may generate an adverse effect that is larger than any positive effect from being willing to deal with complaints.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…This broadcasting tends to prevent customers from posting content that makes them look bad (Barasch and Berger 2014) and increases the likelihood that they blame the firm for the failure. In response, firms strive to resolve complaints as quickly as possible (Herhausen et al 2019) or force the communication into a private complaint channel (Golmohammadi et al 2021) to limit the negative effects in terms of other people reading the complaint exchange. However, it is equally important to examine how such social media response strategies are viewed from the perspective of the complaining customer.…”
Section: Conceptual Development and Hypothesesmentioning
confidence: 99%
“…Gratitude is a strong indicator that the customers' high-arousal emotions have been de-escalated effectively (Xia and Kukar-Kinney 2013). Third, firms often try to move complaining customers to private channels in their public response (Golmohammadi et al 2021), and gratitude as a potential reaction in the public customer reaction to a firm response may be the only visible outcome for readers of complaints.…”
mentioning
confidence: 99%